Perception and Salience of Social Security Contribution Incentives: Evidence from Voluntary Contributions - Ander Iraizoz (CESifo GmbH, 2025)
In this paper, I investigate how individuals perceive the implicit contribution incentives provided by public pension systems. I use the unique setting of the Spanish public pension system, where self-employed workers are allowed to voluntarily determine the level of their Social Security contributions. Using quasi-experimental variations from three pension reforms, I find that most self-employed workers fail to take advantage of the extraordinary contribution incentives available in Spain, and often make suboptimal contribution choices. These results point to substantial challenges in perceiving implicit contribution incentives, which could lead to inefficiencies in raising Social Security contributions. Furthermore, my findings highlight the critical role of salience in improving the perception of contribution incentives, and thereby promoting greater economic efficiency.
Keywords: D91; E21; H55; 330; contribution-benefit linkage; public pension; social security; salience